2016
DOI: 10.2337/db15-1398
|View full text |Cite
|
Sign up to set email alerts
|

PKCζ Is Essential for Pancreatic β-Cell Replication During Insulin Resistance by Regulating mTOR and Cyclin-D2

Abstract: Adaptive β-cell replication occurs in response to increased metabolic demand during insulin resistance. The intracellular mediators of this compensatory response are poorly defined and their identification could provide significant targets for β-cell regeneration therapies. Here we show that glucose and insulin in vitro and insulin resistance in vivo activate protein kinase C ζ (PKCζ) in pancreatic islets and β-cells. PKCζ is required for glucose- and glucokinase activator–induced proliferation of rodent and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 47 publications
1
62
3
Order By: Relevance
“…Studies relevant to the mechanisms of autophagy indicated that mTOR pathway was involved in pancreatic beta cell, myoblasts, gastric cancer cell, and non-small cell lung cancer [23,24,25,26], but the associated research in hepatocytes was rare. To reveal these potential mechanisms, the effect of mTOR signaling pathway was explored.…”
Section: Discussionmentioning
confidence: 97%
“…Studies relevant to the mechanisms of autophagy indicated that mTOR pathway was involved in pancreatic beta cell, myoblasts, gastric cancer cell, and non-small cell lung cancer [23,24,25,26], but the associated research in hepatocytes was rare. To reveal these potential mechanisms, the effect of mTOR signaling pathway was explored.…”
Section: Discussionmentioning
confidence: 97%
“…Studies of intact and dispersed human islets overexpressing AKT directly have shown increased β-cell proliferation [17], and Yap, another activator of AKT/mTOR signaling, appeared to induce proliferation, though nonspecifically in endocrine cells [18]. PKCζ, which is less often studied as part of the PI3K/mTOR cascade, was recently shown to be necessary for “compensatory” human β-cell replication induced by glucose [19]. Indirect activation of Akt by TGFβ has led to context-dependent effects on β-cell proliferation [20], which suggests that ligands such as TGFβ may activate multiple signaling cascades simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…There is robust data indicating that insulin resistance and/or hyperglycemia stimulates β-cell proliferation in rodents [13,19,39]. Porat and colleagues showed that glucose-induced proliferation was regulated by GK metabolism, with increased glycolytic rate causing the β-cell to upregulate proliferative pathways [39].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the knockout of PKCζ in beta cells of mice blocks their proliferation in response to insulin resistance [43]. PKCζ drives beta cell proliferation through activation of mammalian target of rapamycin (mTOR) [42, 43]. Activation of mTOR then increases expression of cyclin-D2, which drives proliferation [44].…”
Section: Pkc In Pancreatic Inflammationmentioning
confidence: 99%